Surveillance of Trypanosoma cruzi infection in Triatomine vectors, feral dogs and cats, and wild animals in and around El Paso county, Texas, and New Mexico. - Felipe Rodriguez; Brenda S Luna; Olivia Calderon; Claudia Manriquez-Roman; Karsten Amezcua-Winter; Jonathan Cedillo; Rebeca Garcia-Vazquez; Itzel A Tejeda; Alvaro Romero; Kenneth Waldrup; Douglas M Watts; Camilo Khatchikian; et al. (Public Library of Science (PLoS), 2021)
The causative agent of Chagas disease, Trypanosoma cruzi, is transmitted by triatomine vectors. The insect is endemic in the Americas, including the United States, where epidemiological studies are limited, particularly in the Southwestern region. Here, we have determined the prevalence of T. cruzi in triatomines, feral cats and dogs, and wild animals, the infecting parasite genotypes and the mammalian host bloodmeal sources of the triatomines at four different geographical sites in the U.S.-Mexico border, including El Paso County, Texas, and nearby cities in New Mexico. Using qualitative polymerase chain reaction to detect T. cruzi infections, we found 66.4% (n = 225) of triatomines, 45.3% (n = 95) of feral dogs, 39.2% (n = 24) of feral cats, and 71.4% (n = 7) of wild animals positive for T. cruzi. Over 95% of T. cruzi genotypes or discrete typing units (DTUs) identified were TcI and some TcIV. Furthermore, Triatoma rubida was the triatomine species most frequently (98.2%) collected in all samples analyzed. These findings suggest a high prevalence of T. cruzi infections among triatomines, and feral and wild animals in the studied sites. Therefore, our results underscore the urgent need for implementation of a systematic epidemiological surveillance program for T. cruzi infections in insect vectors, and feral and wild animals, and Chagas disease in the human population in the southwestern region of the United States.